2005
DOI: 10.1007/s11207-005-2766-y
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Automated Solar Filament Detection And Characterization Code: Description, Performance, And Results

Abstract: We present a code for automated detection, classification, and tracking of solar filaments in full-disk Hα images that can contribute to Living With a Star science investigations and space weather forecasting. The program can reliably identify filaments; determine their chirality and other relevant parameters like filament area, length, and average orientation with respect to the equator. It is also capable of tracking the day-by-day evolution of filaments while they travel across the visible disk. The code wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 19 publications
0
96
2
Order By: Relevance
“…Zirker et al (1997) and Martin (1998) reviewed the fine structures in filaments seen in Hα (studied by e.g., Martin et al 1994), which are considered to reflect the magnetic field in filaments, and concluded that the filament fine structures, particularly barbs of filaments, show a chiral nature that in the northern hemisphere, barbs are right-bearing (dextral), and in the southern hemisphere, they are left-bearing (sinistral). This property of the fine structure in filaments has been further studied and discussed by Pevtsov et al (2003), Bernasconi et al (2005), Yeates et al (2007), and Ouyang et al (2017).…”
Section: Introductionmentioning
confidence: 83%
“…Zirker et al (1997) and Martin (1998) reviewed the fine structures in filaments seen in Hα (studied by e.g., Martin et al 1994), which are considered to reflect the magnetic field in filaments, and concluded that the filament fine structures, particularly barbs of filaments, show a chiral nature that in the northern hemisphere, barbs are right-bearing (dextral), and in the southern hemisphere, they are left-bearing (sinistral). This property of the fine structure in filaments has been further studied and discussed by Pevtsov et al (2003), Bernasconi et al (2005), Yeates et al (2007), and Ouyang et al (2017).…”
Section: Introductionmentioning
confidence: 83%
“…It is beyond the scope of this paper to perform a very sophisticated region extraction such as those realized by Fuller et al (2005), Ipson et al (2005), Bernasconi et al (2005), Aboudarham et al (2008) or Scholl & Habbal (2008), as their purpose was to identify complete filaments as a whole, with Virtual Observatory applications in mind (building of synoptic maps for example, in which the different pieces constituting a filament must be associated and tracked in time). Here we are mainly interested in the total area covered by these structures at a given time, therefore there is no need to associate them.…”
Section: Discussionmentioning
confidence: 99%
“…Although temporal periodic patterns have not been found, some systematics regarding the spatial distribution of helical features on a global scale are known. Several observational features indicating the handedness of structures, such as sunspot whorls (Hale 1925;Richardson 1941, and references therein), chirality of filaments (Rust 1967;Pevtsov and Balasubramaniam 2003;Bernasconi et al 2005) and S-shaped coronal X-ray brightening (Rust and Kumar 1996;Canfield et al 1999) revealed a dominant pos-itive helicity pattern in the northern solar hemisphere and a dominant negative one south of the solar equator. The associated magnetic fields in the northern and southern hemisphere are dominated by right-and left-handedness, respectively (Seehafer 1990;Pevtsov et al 1995).…”
Section: Hemispheric Trendsmentioning
confidence: 97%